Unitarian Universalist Church of Fresno Children with Carved Pumpkins - Watkins, Howard::::::::: (1987)
Church school members on lawn by their jack o'lanterns; Tara Freeman in sleeveless white dress; Robin Watkins in red dress Church at 4144 N. Millbrook Avenue, Fresno